2011
DOI: 10.1590/s1806-37132011000100008
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da pressão positiva expiratória nas vias aéreas sobre a atividade eletromiográfica da musculatura acessória da inspiração em portadores de DPOC

Abstract: Objective: To evaluate the electromyographic activity (EA) of sternocleidomastoid (SCM) and scalene muscles during and after the use of expiratory positive airway pressure (EPAP) in patients with COPD. Methods: This was a clinical single-blind trial involving 13 healthy subjects as controls and 12 patients with stable COPD. At baseline, we determined EA during spontaneous respiration, lung function parameters, and respiratory muscle strength. Subsequently, EPAP at 15 cmH 2 O was applied by means of a face mask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(32 reference statements)
0
1
0
4
Order By: Relevance
“…No significant changes were observed in the control group. In some studies comparing the effects of spontaneous, slow and deep breathing and the use of PEP, no significant differences in oxygen saturation, dyspnoea, blood pressure and pulse were found (Cardoso et al, 2014; Phimphasak et al, 2018; Silva et al, 2020). Studies have also shown a significant decrease in blood pressure and pulse, as well as an increase in oxygen saturation when PEP is used (Ranieri et al, 1993; Zhou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…No significant changes were observed in the control group. In some studies comparing the effects of spontaneous, slow and deep breathing and the use of PEP, no significant differences in oxygen saturation, dyspnoea, blood pressure and pulse were found (Cardoso et al, 2014; Phimphasak et al, 2018; Silva et al, 2020). Studies have also shown a significant decrease in blood pressure and pulse, as well as an increase in oxygen saturation when PEP is used (Ranieri et al, 1993; Zhou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Las mujeres, al contrario, muestran un tiempo de inspiración ligeramente más corto que el tiempo de espiración respecto de los hombres. 21,22,24 Fueron utilizados dos tipos de equipos para medir las PRM, los cuales se consideran válidos y cuentan con algoritmos bien descriptos para su utilización. Si bien varían según la marca, en general, podemos dividir los equipos en manómetro de mercurio y manovacuómetro digital o análogico.…”
Section: Análisis Del Riesgo De Sesgounclassified
“…En ninguno de los estudios, se les pide a los sujetos que coloquen sus manos sobre sus mejillas para evitar la acción de los músculos buccinadores. 22,24 La selección de la posición para realizar la toma de las mediciones se relaciona al estado de salud del sujeto. Es sabido que promedios de edad fueron muy variables.…”
Section: Análisis Del Riesgo De Sesgounclassified
“…Contudo, a realização de estudos específicos em diferentes condições clínicas e/ou cirúrgicas pode ser necessária. Por outro lado, Cardoso et al 19 Apesar da diferença encontrada nas respostas da FC, identificou-se pequena variação dos valores de PA nas diferentes manobras (MV e EPAP). O emprego de metodologia indireta (método auscultatório) para aferição da PA pode ter contribuído para este resultado, tendo em vista que este apresenta limitações em relação à medida direta e contínua da PA, que é a metodologia padrão para a avaliação da resposta da PA durante a execução da MV 20 .…”
Section: Variáveis Média±dpunclassified